EFFECTIVENESS OF WEARING STERILE GLOVES ON PREVENTING MOUTH IRRITATION POST TOOTH EXTRACTION: EFEKTIFITAS PEMAKAIAN SARUNG TANGAN STERIL TERHADAP PENCEGAHAN IRITASI RONGGA MULUT PASCA PENCABUTAN GIGI - Hendri Poernomo; Setiawan (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2022)
The use of gloves in dental practice is imperative to prevent cross-infection between the patient and the operator or vice versa, besides that the use of gloves can prevent irritation of the oral cavity after permanent tooth extraction. The research method used a quasi-experiment with a pre-test and post-test approach with 40 samples. The results showed that 2 people experienced irritation and 28 people who did not experience irritation after permanent tooth extraction using sterile gloves while using non-sterile gloves experienced irritation as many as 3 people out of 10 control samples. Based on the T-test calculation, it was found that the difference was not significant (p>0,05). In the study, the t-count value was 3,808 with a p value of 0,001. Conclusion: The use of sterile gloves can prevent the risk of irritation in permanent tooth extraction patients.